Diagnosis and management of children and young people with familial hypercholesterolaemia. (2nd January 2019) - Priestley-Barnham, Lorraine; Breen, Jane; Neves, Emma; Khan, Tina Z; Barbir, Mahmoud
Abstract : Heterozygous familial hypercholesterolaemia is a common genetic condition characterised by the impaired clearance of low density lipoprotein cholesterol from the bloodstream. Incidence rates can be as high as 1/250 and those confirmed with familial hypercholesterolaemia are predisposed to progressive atherosclerosis throughout childhood, increasing their risk of premature cardiovascular disease. Early identification and initiation of risk factor management and lipid-lowering therapy are fundamental if this risk and its associated comorbidities are to be reduced and a life expectancy similar to that of the general population restored. This article discusses several aspects of familial hypercholesterolaemia including identification, diagnosis through genetic testing and treatment protocols in a tertiary cardiac centre. It aims to share key learning points with other institutions either already established in the care of paediatric patients with familial hypercholesterolaemia or those contemplating forming a service to meet the needs of this growing cohort.